MODEL OF LANGUAGE BULLYING IN EFL CLASSROOM: A CASE STUDY OF JUNIOR HIGH SCHOOL - Mukarramah, Sofiyatul (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2025)
This study employs Case Study to investigate this during question and answer interactions in EFL. The model of language bullying in EFL classrooms illustrates how students may experience harassment based on language skills or accents, leading to emotional and academic challenges. It encompasses various forms of bullying, such as verbal abuse, exclusion, and ridicule, often stemming from peer dynamics and cultural differences. Addressing this issue involves creating awareness, promoting empathy, and implementing strategies that foster a respectful learning environment, ultimately encouraging all students to feel safe and engaged in their language learning journey. The case study on language bullying in EFL classrooms at a junior high school explores how language-related teasing and discrimination affect students' learning experiences. It identifies key factors contributing to this behavior, such as proficiency disparities and social hierarchies among peers. The findings suggest that language bullying not only impacts students' confidence but also their engagement in learning. To combat this, the study advocates for interventions that promote inclusivity and respect, ultimately aiming to create a supportive classroom atmosphere.